2021
DOI: 10.1155/2021/8873169
|View full text |Cite
|
Sign up to set email alerts
|

Chest-to-Back Skin-to-Skin Contact to Regulate Body Temperature for Low Birth Weight and/or Premature Babies: A Crossover Randomized Controlled Clinical Trial

Abstract: Skin-to-skin contact (SSC) is one of the critical components of kangaroo mother care (KMC), which is an intervention to enhance the survival of low birth weight (LBW) and/or premature infants in low-income settings. Chest-to-chest (CC) contact has been practiced widely; however, mothers face practical challenges to continuously provide CC-SSC. Hence, we assessed the efficacy of chest-to-back (CB) SSC as an alternative to CC-SSC in regulating body temperature for LBW and/or premature babies in Ethiopia. We appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…Skin-to-skin contact provides that condition; the front body skin and the back body skin of an adult human being have identical thermal comfort [ 38 ]. We have also shown that the CB SSC and CC SSC have similar warming effects [ 8 ]. Studies also show that CC SSC stabilizes the oxygen saturation and the heart rate of babies in a clinically acceptable range [ 3 , 25 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Skin-to-skin contact provides that condition; the front body skin and the back body skin of an adult human being have identical thermal comfort [ 38 ]. We have also shown that the CB SSC and CC SSC have similar warming effects [ 8 ]. Studies also show that CC SSC stabilizes the oxygen saturation and the heart rate of babies in a clinically acceptable range [ 3 , 25 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in Ethiopia [ 27 ]. The details of the methods are presented in our previous paper [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations